HUBUNGAN FAKTOR INTIMASI DAN PASSION DENGAN PERILAKU PACARAN PADA REMAJA - Wiwik U, Wiwik U; Yeni K, Yeni K; Eva Nur Hidayati Ni’mah, Eva Nur Hidayati Ni’mah (Jurnal Penelitian Kesehatan, 2013)
Need for affection is one of the basic human needs. Dating is an introduction between two human beings on stage matches the search towards married life. But in fact, the application process is still very far from the goal, there are many teenagers who behave wrong in dating. The purpose of the study to analyze the correlation between intimacy and passion with dating behavior of adolescents.The study design using analytic correlate, the entire student population of Nursing Diploma Program Health Academy Rajekwesi Bojonegoro level III, 77 samples Respondents. Sampling using simple random sampling technique. Methods of data collection using questionnaires and observation, then the data were analyzed using a statistical test for contingency coefficient promoted relationships between variables.Â results through statistical tests of contingency coefficient obtained significance value (p) = 0.001 <Î± = 0.05. H0 is rejected, it means that there is a correlation factor of intimacy with dating behavior. (p) = 0.010 <Î± = 0.05. H0 is rejected, it means that there is a correlation factor of passion with dating behavior in adolescents.Conclusion The research is adolescent courtship behavior can be affected whether or not the dominant factor of intimacy and passion. Teenagers are advised to increase positive behaviors in dating relationships that are healthy.Â Keywords: Intimacy, passion, dating, Â teens.Â